2019
DOI: 10.1029/2018jc014567
|View full text |Cite
|
Sign up to set email alerts
|

Variability of the Pacific‐Derived Arctic Water Over the Southeastern Wandel Sea Shelf (Northeast Greenland) in 2015–2016

Abstract: A portion of the freshwater transport through Fram Strait consists of low-salinity Pacific-derived Arctic water flowing southward along the east coast of Greenland. The pathways of this water are currently unclear. An Ice Tethered Profiler deployed over the southeastern Wandel Sea shelf (northeast Greenland) in May 2015 collected a profile every 3 hr for a year recording conductivity-temperature-depth (CTD) and Colored Dissolved Organic Matter (CDOM) fluorescence. This was accompanied by velocity observations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 75 publications
(126 reference statements)
2
14
0
Order By: Relevance
“…This assumption defines how Greenland discharge is added in the model, injected at the surface level then mixed into a 10 m thick layer. This approach is common in the present generation of ocean models at this horizontal scale, such as in Castro de la Guardia et al (2015) and Dukhovskoy et al (2016). Observations (Beaird et al, 2017(Beaird et al, , 2018 have shown that freshwater may not only be at the surface but be mixed and entrained with ambient waters and find a neutral buoyancy at depth.…”
Section: Control Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…This assumption defines how Greenland discharge is added in the model, injected at the surface level then mixed into a 10 m thick layer. This approach is common in the present generation of ocean models at this horizontal scale, such as in Castro de la Guardia et al (2015) and Dukhovskoy et al (2016). Observations (Beaird et al, 2017(Beaird et al, , 2018 have shown that freshwater may not only be at the surface but be mixed and entrained with ambient waters and find a neutral buoyancy at depth.…”
Section: Control Experimentsmentioning
confidence: 99%
“…Meltwater originating off the southwestern coast of the GrIS has been shown to circulate into the interior of the Labrador Sea (Gillard et al, 2016;Böning et al, 2016;Luo et al, 2016;Dukhovskoy et al, 2016). The Labrador Sea convection region is sensitive to changes in buoyancy, a balance between heat loss and freshwater input (Aagaard and Carmack, 1989;Straneo, 2006;Weijer et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, contribution of sea-ice meltwater to the surface water of the Nordic Seas was evaluated by an in situ threechannel fluorometer (Makarewicz et al, 2018). In addition, Pacific water outflow from the Arctic Ocean, which contains high levels of FOM H , was determined in the southeastern Wandel Sea Shelf, northeast Greenland, with an in situ fluorometer (Dmitrenko et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Upwelling winds also cause intense mixing of a river plume with subjacent saline sea due to increased velocity shear and an Ekman straining mechanism [58,63]. Therefore, upwelling events along coastal areas influenced by freshwater discharge significantly affect spreading and mixing of river plumes, as well as the local nutrient cycle, biological consumption, food webs, and biological productivity [56,[64][65][66][67][68].Many previous works addressed wind-driven coastal upwelling events in the Arctic Ocean [19,[69][70][71][72][73][74]. However, interaction between river plumes and coastal upwelling in the Arctic Ocean remain mainly unstudied.…”
mentioning
confidence: 99%
“…Many previous works addressed wind-driven coastal upwelling events in the Arctic Ocean [19,[69][70][71][72][73][74]. However, interaction between river plumes and coastal upwelling in the Arctic Ocean remain mainly unstudied.…”
mentioning
confidence: 99%